(untitled) (Gestão & Regionalidade, 2023)
This article analyzes the public policies for the promotion of the Local Productive and Innovative Arrangement and System - ASPIL of artifacts and garments of colored cotton from Paraíba, from the scalar perspective of development. To this end, a survey was designed using a field, with the application of interviews and questionnaires to collect data, in addition to a literature review. It was found that the ASPIL analyzed here was developed based on strategies of local public agencies. However, after 2010, the lack of public policies to support the arrangement culminated in the widening of barriers. Even so, the companies in the arrangement have stood out in the international fashion scene, due to partnerships with the actors of the macro scale. On the other hand, since 2016, public policy has been structured with a multi-scalar view of promoting the arrangements, as it is understood that the analysis from the scales, provides the guidance of development policies.